Socio-Demographic Factors of Parents Influencing Childhood Immunization in Enugu State, Nigeria - C. N., Ngwu (Journal of Home Economics Research, 2024)
The purpose of this study was to examine the socio-demographic factors of parents that influence childhood immunization in Enugu State, Nigeria. The study population consisted of married women of childbearing age (18-49) and their husbands. A sample of 1000 respondents was selected. Questionnaire was used for data collection. Focus Group Discussions (FGD) sessions were also conducted. Quantitative data were analyzed using percentages. Findings showed, among others, that female respondents (62.6%) perceived immunization as very important to their children as against their male counter-parts (37.4%). Younger respondents (72.5%) perceived immunization as more important than older respondents (27.5%). It is recommended that Enugu State Government needs to strengthen the expanded programme on immunization in the state with the aims of mobilizing, sensitizing, and convincing the older respondents of childbearing age to reduce drastically the number of deaths among children arising from preventable diseases.